2016
DOI: 10.11114/jets.v4i9.1672
|View full text |Cite
|
Sign up to set email alerts
|

Perception of ‘English’ and Motivation in Learning English

Abstract: This study aims to present high school students" perception of "English" through the impressions and images and the effect of these perceptions on their motivation in learning English. This qualitative study is based on the data about students" metaphors and the focus group interview to determine their effect on the students" motivation. The research group for metaphors consists of 128 high school students from four different grades. 79 metaphors were collected and grouped under 12 categories. In addition, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The others, on the other hand, might find themselves inadequate in the FL, as they could not improve their language skills most probably because of insufficient practice, which in the end will result in anxiety. Similarly, Şahin, Seçer and Erişen (2016) found that the students who have positive perceptions of English join in the lessons more and are more motivated compared to other students who perceive English negatively and construct negative metaphors around it. The similarity between the two studies is that, since the participants have a positive perception, they are more willing to join in the FL lessons.…”
Section: Quantitative Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The others, on the other hand, might find themselves inadequate in the FL, as they could not improve their language skills most probably because of insufficient practice, which in the end will result in anxiety. Similarly, Şahin, Seçer and Erişen (2016) found that the students who have positive perceptions of English join in the lessons more and are more motivated compared to other students who perceive English negatively and construct negative metaphors around it. The similarity between the two studies is that, since the participants have a positive perception, they are more willing to join in the FL lessons.…”
Section: Quantitative Resultsmentioning
confidence: 84%
“…Another attention-catching point revealed in the research was that some students quit optional language studies at school, as their teachers were not able to motivate them enough. In another study, Şahin, Seçer and Erişen (2016) examined high school students' perception of English with their impressions and images as well as the effect of these perceptions on their motivation to learn English. The results of this study showed that the students who perceive English positively, participate more and are highly motivated in comparison to students who have negative perceptions and construct negative metaphors to describe their perceptions.…”
Section: Perception Of Foreign Language Learningmentioning
confidence: 99%
“…Those who did not want to learn English cited some reasons as not understanding it and finding it difficult. Students who have no problem with understating English generally have positive attitudes towards it (Şahin, Seçer & Erişen, 2016). Few students had a negative attitude towards English, which caused them lack of motivation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Alizadeh (2016), the most relevant factor for teaching a foreign language is the motivation for learning. However, students tend toward a low motivation for learning because they focus on diagnostic tests and grades rather than English as a culture and worthy communicational resource (Sahin et al, 2016). Motivation and Demotivation are concepts related to the presence or lack of interest of a person in doing any activity until finish it.…”
Section: Students' Motivation For Learning English Languagementioning
confidence: 99%